2021
DOI: 10.1213/ane.0000000000005416
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Hematocrit and Adverse Outcomes in Pediatric Cardiac Surgery Patients: A Cross-Sectional Study From the Society of Thoracic Surgeons and Congenital Cardiac Anesthesia Society Database Collaboration

Abstract: BACKGROUND: We sought to examine potential associations between pediatric postcardiac surgical hematocrit values and postoperative complications or mortality. METHODS: A retrospective, cross-sectional study from the Society of Thoracic Surgeons Congenital Heart Surgery Database (STS-CHSD) and Congenital Cardiac Anesthesia Society Database Module (2014–2019) was completed. Multivariable logistic regression models, adjusting for covariates in the STS-CHSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…This was possibly influenced by the critical HES discussion in intensive care medicine leading to a more restrictive use of artificial colloids, including in pediatric anesthesia. From a clinical point of view, underestimation of blood loss, low tissue perfusion, fluid overload, and adverse effects caused by blood transfusion are relevant risks during major pediatric surgery, 15,16,35 whereas this study showed—in accordance with our previous HES study 5 —that postoperative renal failure caused by artificial colloids seems to be very unlikely in hemodynamically stable children with normal renal function.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This was possibly influenced by the critical HES discussion in intensive care medicine leading to a more restrictive use of artificial colloids, including in pediatric anesthesia. From a clinical point of view, underestimation of blood loss, low tissue perfusion, fluid overload, and adverse effects caused by blood transfusion are relevant risks during major pediatric surgery, 15,16,35 whereas this study showed—in accordance with our previous HES study 5 —that postoperative renal failure caused by artificial colloids seems to be very unlikely in hemodynamically stable children with normal renal function.…”
Section: Discussionsupporting
confidence: 88%
“…Presently, there is a strong trend to limit fluid overload and transfusion of blood products to improve the postoperative recovery and outcome of children undergoing major pediatric surgery. 15,16 Additionally, the findings of the Pediatric Perioperative Cardiac Arrest (POCA) Registry revealed that hypovolemia from underestimated blood loss and hyperkalemia from blood transfusion were the most common causes of perioperative cardiac arrest. 17 Although the current evidence on the choice of fluids for resuscitation in children is weak, our study showed that the perioperative use of moderate doses of GEL in combination with crystalloids and vasoactive drugs improves hemodynamic stability and contributes to limit the total infusion and transfusion volume in children undergoing major pediatric surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent retrospective study demonstrated that each 5% increase in ICU arrival hematocrit greater than 38% for acyanotic and 42% for cyanotic children was associated with a significant increase in the odds of perioperative mortality and major complications. 22 While this retrospective study can only demonstrate an association of worse outcomes with higher intraoperative hemoglobin level, it highlights the need for prospective studies with well defined perioperative transfusion guidelines reserving transfusions for patients with clinical evidence of poor oxygen delivery and avoiding overtransfusion in clinically stable patients.…”
Section: Pediatric Cardiac Surgical Patientsmentioning
confidence: 86%
“…[19][20][21] In fact, perioperative erythrocyte transfusions often result in higher hemoglobin levels than even "liberal" transfusion thresholds. [20][21][22] Therefore, the development of universal, specific, evidenced-based perioperative hemoglobin management and erythrocyte transfusion guidelines for the anemic and/or bleeding pediatric patient would standardize care, reduce practice variability, and potentially improve safety.…”
mentioning
confidence: 99%